2020
DOI: 10.1038/s41598-020-66132-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and modules in response to Cadmium stress in different rice varieties and stem nodes by weighted gene co-expression network analysis

Abstract: Soil cadmium (Cd) pollution threatens food safety. This study aimed to identify genes related to Cd accumulation in rice. Low-(Shennong 315, short for S315) and high-(Shendao 47, short for S47) Cd-accumulative rice cultivars were incubated with CdCl 2 •2.5H 2 O. RNA-seq and weighted gene coexpression network analysis (WGCNA) were performed to identify the modules and genes associated with Cd-accumulative traits of rice. After Cd stress treatment, the Cd content in various tissues of S315 was significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
1
22
0
1
Order By: Relevance
“…analyses (DalCorso et al, 2010;Huang et al, 2012;Yu et al, 2012;Deng et al, 2020;Wang et al, 2020). Usually, the regulatory networks consist of rapidly activated ROS production and calcium (Ca) oscillation, which can be perceived by Ca-binding proteins and magnified via kinases and further downstream pathways such as phytohormones, transport systems, and ROS scavenging, are precisely modulated to induce an appropriately reactive physiological response (Deng et al, 2020).…”
Section: Regulatory Components Of Ja-responsive Signaling Pathways In Response To Toxic Elementsmentioning
confidence: 99%
“…analyses (DalCorso et al, 2010;Huang et al, 2012;Yu et al, 2012;Deng et al, 2020;Wang et al, 2020). Usually, the regulatory networks consist of rapidly activated ROS production and calcium (Ca) oscillation, which can be perceived by Ca-binding proteins and magnified via kinases and further downstream pathways such as phytohormones, transport systems, and ROS scavenging, are precisely modulated to induce an appropriately reactive physiological response (Deng et al, 2020).…”
Section: Regulatory Components Of Ja-responsive Signaling Pathways In Response To Toxic Elementsmentioning
confidence: 99%
“…Finally, we tested for associations with climate terms between, within, and variably across clusters for FLC/SOC1 expression, these residual gene expression PCs, and S1. Congruence of 13 genomic clusters identified and used in this study with the ancestry groups found by the 1001 Genomes Consortium [39]. Percentages indicate the percent of a given genomic cluster in each ancestry group, color coded by the number of accessions in a given group.…”
Section: Gene Expression and Flowering Timementioning
confidence: 99%
“…Thus, another effective method for more deeply examining signals of local adaptation is by interrogating environmental associations among genes with co-varying expression levels clustered into gene co-expression networks (33). With sufficient data, gene co-expression modules can then be connected to environmental agents of selection through clinal analysis (34)(35)(36)(37), to underlying polymorphisms through association mapping (38), and to organismal phenotypes through correlational tests or analyses of enrichment for particular gene functions (39,40). Moreover, different co-expression modules may orthogonally influence variation in subcomponents of a more integrated trait or trait syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene co-expression networks derived through WCNA analysis have emerged as a robust systems biology approach to discover associations within biomolecules [41][42][43][44][45][46][47][48]. As demonstrated by the guilt-of-association concept, genes with similar expression patterns are most likely to be associated with a similar biological process [49,50].…”
Section: Network-based Characterization Of Transcriptome and Metabolome Relationships In Mallotus Japonicusmentioning
confidence: 99%